Examining pedagogical knowledge content on mitosis in a University context - González, Norma Viviana (2016)
Mitosis is a process of cell division occurring in eukaryotic organisms. Students from many countries experience difficulties learning this science topic, and its teaching demands substantial effort. Effective teachers develop a wide range of knowledge types to successfully transform science matter for students; this transformation of knowledge has been conceptualized as pedagogical content knowledge (PCK). In this study the PCK of two University teachers on mitosis was explored. As informed by the instruments employed (Content Representation and Pedagogical (CoRe), and Professional experiences Repertoires, analytical rubric (PaP-eR), and semi-structured interviews) both participants’ PCK on mitosis can be characterized as incomplete, however not identical. PCK evolves throughout the professional practice so, in a context mostly limited to a traditional teacher-centered transmission of knowledge such as the university, development of teachers’ PCK emerges as a strategy to reorient the teaching of mitosis to modalities based on the construction of scaffoldings to facilitate students’ learning.